Emission of Fumes of Ursus MF235 under Conditions of Load with The Use of a Movable Dynamometric Stand (Agricultural Engineering, 2017)
The article presents calculations of unit fumes emission made based on the measurements of the fumes composition during a load test. The test was carried out with the use of a movable dynamometric stand adjusted for testing agricultural tractors by power take-off shaft. Calculations of unit emission were made based on the assumed flow of air sucked by an engine and the measured composition of fumes emitted during the load test. Results of tests and analyses supply information on the mass of particle matter and the selected gas elements emitted by an engine working under the load which was related to simultaneous determination of the exploitation characteristic of an engine. The presented methodology may be helpful at evaluation of impact of farm tractors on the environment within the hazardous fume components emitted by them.